Comparison of Mind Mapping and Inside Outside Circle Learning Model on Mathematical Communication Students' - Lestari, Puji; Irfadillah, N Mutiara (Universitas Sebelas Maret, 2020)
The purpose of this study is to examine the two models' implementation for students'mathematical communication skills. The research method used was a quasi-experiment with a sample of 62 students selected by purposive sampling from two classes, namely Mind Mapping class and Inside-Outside Circle class. The instrument used was a test description of mathematical communication skills and a validated questionnaire. The results showed that the mathematical communication skills of students who obtained Mind Mapping and Inside-Outside Circle learning models did not differ significantly, with the quality of improving mathematical communication skills of the two classes based on the normalized gain test being in the medium category. When viewed from the frequency of students who reach the KKM, both are still less than 75%, so the two learning models' implications cannot be said to be good. However, students'responses to the learning models provided showed reactions with the right interpretation.